Forest-to-agriculture conversion in Amazon drives soil microbial communities and N-cycle. (October 2019) - Merloti, Luis Fernando; Mendes, Lucas William; Pedrinho, Alexandre; de Souza, Leandro Fonseca; Ferrari, Beatriz Maria; Tsai, Siu Mui
Abstract: Soil microorganisms play an important role in the N cycle; however, these communities are sensitive to soil disturbances. Understanding the influence of anthropogenic activities on soil microbial communities would increase our ability to establish conservation strategies in the Amazon region, where deforestation has become a great concern. We hypothesized that forest-to-agriculture conversion in a short- and long-term is responsible for alterations in soil chemical properties, with consequences on the composition, diversity, and potential function of microbial communities. Here, we used 16S rRNA amplicon sequencing and quantitative PCR to assess the bacterial and archaeal composition, diversity, abundance, and the potential functions related to the N-cycle in a natural forest and agricultural fields with 2-, 8-, and 20-years after conversion in the Amazon region. We observed that soil chemical properties were altered by the forest-to-agriculture conversion, which consequently affected the bacterial and archaeal communities. In general, Ca, Al, NH4 +, and N-total were significantly correlated to the overall microbial community structure. Forest-to-agriculture conversion also altered the microbial composition and potential functions related to the N-cycle, increasing the nitrification and denitrification processes in agricultural soils, while natural forest demonstrated to be a potential N2 O sink. Together, our data demonstrated the impacts of forest-to-agriculture conversion in the Amazon region and add important information for future research that seeks the development of more sustainable agriculture. Highlights: Forest-to-agriculture conversion in the Amazon shapes microbial community structure. Ca and Al are key elements shaping microbial community in these soils. Agriculture presents higher abundance of nitrification and denitrification genes. Forest is a potential sink of N2 O.